UF4 and the High‐Pressure Polymorph HP‐UF4. Issue 30 (3rd May 2019) - Scheibe, Benjamin; Bruns, Jörn; Heymann, Gunter; Sachs, Malte; Karttunen, Antti J.; Pietzonka, Clemens; Ivlev, Sergei I.; Huppertz, Hubert; Kraus, Florian
Abstract: A laboratory‐scale synthesis of UF4 is presented that utilizes the reduction of UF6 with sulfur in anhydrous hydrogen fluoride. An excess of sulfur can be removed by vacuum sublimation, yielding pure UF4, as shown by powder X‐ray diffraction, micro X‐ray fluorescence analysis, infrared and Raman spectroscopy, as well as magnetic measurements. Furthermore, a single‐crystalline, high‐pressure modification of UF4 was obtained in a multi‐anvil press at elevated temperatures. The high‐pressure polymorph HP‐UF4 was characterized by means of single‐crystal and powder X‐ray diffraction, as well as by magnetic measurements, and presents a novel crystal structure type. Quantum‐chemical calculations show the HP‐modification to be 10 kJ mol −1 per formula unit higher in energy compared to UF4 . Abstract : Uranium under pressure : The reaction of UF6 with S8 in anhydrous HF under oxygen‐free conditions yields UF4 of high purity. Subsequent treatment of the obtained UF4 in a multi‐anvil press yields the high‐pressure modification HP‐UF4 in single‐crystalline state, with unusual coordination environments for the uranium atoms. Both compounds are investigated by magnetic measurements and quantum‐chemical calculations.